Chemical compounds and antimicrobial activities of actinomycetes isolates from BRIS soil - Hamidah Idris (Tanjung Malim, 2021)
Chemical compounds and antimicrobial activities of actinomycetes isolates from BRIS soil by Hamidah Idris